Phase 2 trial of hypoxia activated evofosfamide (TH302) for treatment of recurrent bevacizumab-refractory glioblastoma - Andrew J. Brenner (Nature Portfolio, 2021)
Abstract Evofosfamide (Evo or TH302) is a hypoxia-activated prodrug which is reduced leading to the release of alkylating agent bromo-isophosphoramide mustard, which has shown safety and signals of efficacy in a prior phase 1 study in recurrent glioblastoma. We performed a dual center single-arm Phase II study to expand on the safety and efficacy of Evo plus bevacizumab in bevacizumab refractory glioblastoma. 33 patients with bevacizumab refractory GBM received Evo 670 mg/m2 in combination with Bevacizumab 10 mg/kg IV every 2 weeks. Assessments included adverse events, response, and survival. Median age of patients was 47 (range 19–76) and 24 (69%) were male. At the time of study entry, 9 (26%) had ongoing corticosteroid use. ECOG performance status was 0 or 1 in 83% of patients. Patients were mostly heavily pretreated with 77% have three or more prior regimens. A total of 12 patients (36%) suffered grade 3–4 drug associated adverse event (AE); no grade 5 AE were reported. Of the 33 evaluable patients, best response was PR in 3 (9%), SD in 14 (43%), and PD in 16 (48%) with responses confirmed by a second reviewer. Median time to progression of disease was 53 days (95% CI 42–113) and Median time to death was 129 days (95% CI 86–199 days). Progression free survival at 4 months (PFS-4) on Evo-Bev was 31%, which was a statistically significant improvement over the historical rate of 3%. The median overall survival of patients receiving Evo-Bevacizumab was 4.6 months (95% CI 2.9–6.6). The progression free survival of patients on Evo-Bevacizumab met the primary endpoint of progression free survival at 4 months of 31%, although the clinical significance of this may be limited. Given the patient population and Phase II design, these clinical outcomes will need further validation.